Life sciences industry : from laboratories to commercialization of research - Bahera, Basanta Kumara; Prasad, Ram (Professor of microbiology); Behera, Shyambhavee (New paradigms of living systems,, 2021)
Basic principles of applied life sciences such as recombinant DNA technology is used in most life sciences industries marketing bio-formulations for designing more effective protein-based drugs, such as erythropoietin and fast-acting insulin etc. In recent times genetically engineered host cells from mammal, animal and plants are also being used in life sciences industries to manufacture biologics. This book discusses the most basic as well advanced issues on biological products for successfully managing a life sciences industry. It elucidates the life cycle of biological molecules, right from the conceptual development of different types of biopolymers, and their subsequent transfer from the conical flasks in laboratory to life sciences industries for large scale production and marketing. It focuses on sustainable longevity in the life cycle of commercial biopolymers. Cumulative facts and figures in this volume would immensely help in inspiring life sciences industry promoters to monitor value chain transfer process of biologics for better profitability. Additionally, it would serve as a perusal document for the students and researchers interested in entrepreneurial ventures or having their own start-up projects for the commercialization of biologics. .